(untitled) (Research, Society and Development, 2022)
Background: SARS-CoV-2 disease can lead to respiratory failure and the need for mechanical ventilation. Pneumonia caused by Covid-19 presents with 2 phenotypes that course with different pathophysiology, type 1 and type 2. Aim: The objective of the study was to correlate the phenotypic profile of patients with acute respiratory distress syndrome diagnosed with Covid-19. 19 and their outcomes. Methods: This is an analytical retrospective cross-sectional study, which used clinical data from ICU patients at Hospital das Clínicas, Universidade Federal de Pernambuco. Data were described in simple frequencies. The correlation between hospitalization and pulmonary physiology variables with clinical outcome was tested using Pearson’s chi-square test. For variables with a significant association, logistic regression was performed with the outcome of ICU discharge, and the results were presented with odds ratio. Results: An association was observed between death and patients aged > 60 years (p=0.003), length of stay ≤ 11 days (p=0.001) and static compliance ≤ 35 ml/cmH2O (p=0.045). Multiple logistic regression with the high outcome found significant values for compliance ≤ 35 ml/H2O (p-value=0.029) and length of stay ≤ 11 days (p=0.014). Conclusion: in the present study, it was observed that the factors age greater than 60 years, shorter hospital stay and lower lung compliance were associated with the outcome of death in patients with Covid-19.